The Current Status and Structural Analysis of College Students’ Employability - Li, Chan; Jansaeng, Apiradee (Journal of Ecohumanism, 2024)
Abstract With the rapid development of the social economy and the advent of the knowledge economy era, the employability of college students has become a key indicator for measuring the quality of higher education and promoting social progress. Currently, improving the employability of college students is not only related to their personal development but also to the overall level of the national innovation system and economic construction. This study aims to explore the employability of students at Liuzhou Vocational and Technical College. Through random sampling, we surveyed 300 recent graduates (covering various majors) and 200 previous graduates (covering various majors) from Liuzhou Vocational and Technical College, and invited 10 companies that hired graduates from the college to participate in an online questionnaire survey. We also conducted interviews with five companies that recruit graduates from Liuzhou Vocational and Technical College to analyze in depth the current status of college students' employability, covering aspects such as cognitive ability, professional skills, social skills, and innovative spirit. The research results show that college students have rich theoretical knowledge but lack soft skills such as teamwork, problem-solving ability, interpersonal communication skills, and coordination ability. To address these issues, this paper proposes the development of training courses to enhance the employability of college students.